Aggressive Intestinal Symptoms Caused by Metastatic Tumors Originating from Primary Gastric Cancer in Pregnancy: A Case Report - Chunlin Zhao; Jingru Ji; Shenghui Lu; Fang Wang; Hailan Yang (Maternal-Fetal Medicine)
Abstract. Gastric carcinoma is extremely rare in pregnancy and the prognosis for this malignancy tends to be dismal. We herein describe a case of gastric cancer in pregnancy to alert clinicians to this rare possibility. A 29-year-old woman developed abdominal spastic pain and diarrhea during the 26 weeks of gestation and her condition was confusing and hard to recognize. The patient was initially misdiagnosed as enterogastritis and inflammatory intestinal obstruction and was finally confirmed by exploratory laparotomy with intestinal and peritoneum metastases. Because the disease was not detected early enough and progressed rapidly, the pregnancy was terminated by cesarean section at 30 weeks of gestation, and then followed by systemic chemotherapy, but eventually succumbed to the lethal pneumonia. Therefore, it is of great significance to alert clinicians to note this rare possibility and to consider the differential diagnosis of this disease in pregnant women with a long course of gastrointestinal symptoms that cannot be explained by pregnancy alone, and cancer should be suspected and tested with sophisticated diagnostic procedures.